ANALISIS KEMAMPUAN KINERJA SISWA SMP DALAM PEMBELAJARAN IPA BERBASIS PROYEK STEM - Suryana, Andri (2017)
The challenges of the 21st century demands the presence of the generation of a nation that has integrity and empowered global competitiveness. One of the domains which can answer the demands is through the realm of education. The Government through its curriculum has facilitated the formation of a generation in order for teamwork and empowered the global competitiveness, including by presenting the education system that also places emphasis on psychomotor aspect or skill that involves performance. But the fact the different field with the desired expectations, based on the preliminary results of a study conducted in once one junior high school by using the now they that lack of learning that supports increased psychomotor domain competency in particular skill involving the ability of performance. To answer these problems then conducted research in order to reveal the performance of JUNIOR HIGH SCHOOL students for the profile and then analyzed. This research was conducted with project-based learning puts a STEM which is divided in two stages, namely the activities activities process design and process performance. As for the design used in this study i.e. one-shot case study design, providing treatment in a group and observed results. As for the results obtained based on research conducted revealed that through project-based learning activities STEM students gained an average score of 2.49 or in percentage of 62.41% of the maximum score and on the activities of the process performance of 3.13 or 78.28%, both categories include both. It undertook to show that students are already good performance ability. The acquisition of these profiles can be asked to provide information or an overview for educators or educational unit in determining the alternative learning IPA (Physics) using project-based learning in the STEM. ---- Tantangan abad ke-21 menuntut hadirnya generasi suatu bangsa yang berintegritas dan berdaya saing global. Salah satu ranah yang dapat menjawab tuntutan tersebut ialah melalui ranah pendidikan. Pemerintah melalui kurikulumnya telah memfasilitasi agar terbentuknya generasi yang berintegritas dan berdaya saing global tersebut, diantaranya dengan menghadirkan sistem pendidikan yang turut menekankan pada aspek psikomotor atau keterampilan yang melibatkan kinerja. Akan tetapi fakta lapangannya berbeda dengan harapan yang diinginkan, berdasarkan hasil studi pendahuluan yang dilakukan disalah satu sekolah menengah pertama dengan menggunakan angket terindikasi bahwa kurangnya pembelajaran yang mendukung peningkatan kompetensi ranah psikomotor khususnya keterampilan yang melibatkan kemampuan kinerja. Menjawab permasalahan tersebut maka dilakukan penelitian guna mengungkap profil kinerja siswa SMP untuk kemudian dianalisis. Penelitian ini dilakukan dengan menghadirkan pembelajaran berbasis proyek STEM yang dibagi dalam dua tahap kegiatan, yakni kegiatan proses desain dan proses kinerja. Adapun desain yang digunakan dalam penelitian ini yaitu one-shot case study design, yakni memberikan perlakuan pada suatu kelompok dan selanjutnya diobservasi hasilnya. Adapun hasil yang diperoleh berdasar penelitian yang dilakukan terungkap bahwa melalui kegiatan pembelajaran berbasis proyek STEM siswa memperoleh skor rata-rata 2,49 atau dalam persentase sebesar 62,41% dari skor maksimum dan pada kegiatan proses kinerja sebesar 3,13 atau 78,28% yang keduanya termasuk kategori baik. Hal tersebut turut menunjukan bahwa kemampuan kinerja siswa sudah baik. Perolehan profil tersebut dapat diajukan untuk memberikan informasi atau gambaran bagi pendidik maupun satuan pendidikan dalam menentukan alternatif pembelajaran IPA (fisika) menggunakan pembelajaran berbasis proyek STEM.